2011
DOI: 10.3892/mmr.2011.624
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin induces apoptosis via the p53 pathway and generation of reactive oxygen species in human osteosarcoma cells

Abstract: Abstract. Osteosarcoma, which is the most common primary bone tumor, occurs most frequently in adolescents. A number of studies have indicated that plumbagin (PL) (5-hydroxy-2-methyl-1, 4-naphthoquinone), a compound found in the plants of the Plumbaginaceae and Droseraceae families, possesses anticancer activity. However, its anticancer effects and mechanisms against osteosarcoma have not been explored. To determine the anticancer effect of PL on osteosarcoma cell lines MG-63 and U2OS, cell viability, apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…ROS has been reported to play pivotal roles in phytochemical-induced cell cycle arrest and apoptosis [23, 24]. Therefore, whether 6-gingerol induced ROS production in LoVo cells was also analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…ROS has been reported to play pivotal roles in phytochemical-induced cell cycle arrest and apoptosis [23, 24]. Therefore, whether 6-gingerol induced ROS production in LoVo cells was also analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…PL has been described to bind to the active site of ER-alpha in BRCA1-blocked BG1 ovarian cancer cells [40]. One of the key mechanisms of apoptosis induction by PL has been linked to ROS production in cells [18-19, 28, 41]. It has been shown that the ROS scavengers or inhibitors e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, plumbagin has been reported to exert anticancer activity on osteosarcoma cells by inducing proapoptotic signaling and modulating the intracellular ROS that causes induction of apoptosis [92]. Moreover plumbagin-induced AMPK activation might be the key mediator of plumbagin's antitumor activity [93].…”
Section: Antioxidant Therapymentioning
confidence: 99%